Oral health in Diadema, Brazil: from schoolchildren dentistry to family health strategy - Cunha, Bernadete Aparecida Tavares; Marques, Regina Auxiliadora de Amorim; Castro, Claudio Gastão Junqueira de; Narvai, Paulo Capel (Saúde e Sociedade, 2011)
Although oral health policy in the city of Diadema, São Paulo, Brazil, from 1972 to 2007, the subject of this article, has accompanied the process of transformation of the sector's practices in Brazil, its evolution in this industrial city located in the metropolitan region of São Paulo has been marked by the singularity of the local history. This paper analyzes this evolution and relates it to the process of social struggles that led to the creation of the Sistema Único de Saúde (Brazil's National Health System) and to the national, state and local oral health policies. This is a qualitative exploratory study. Data were obtained from official documents and various literature sources and also through semi-structured interviews with mayors, municipal health secretaries, oral health coordinators and dentists who have undergone the various stages of the oral health policies in the municipality. The major features in the organization of health care practices developed in the city were identified, locating them in the state and national scenario. We conclude that, despite the consolidation of the integration of oral health in the SUS and the experience acquired in the city in managing this type of care, in Diadema we also observed difficulties to overcome the model of care focused on population groups which have been traditionally prioritized, with emphasis on school children, preschoolers and babies. In this sense, Diadema shares with other Brazilian cities the challenge of restructuring primary care in oral health, overcoming the traditional model of school dentistry and creating new possibilities, such as the family approach, in order to ensure the universality and comprehensiveness of care.